Challenges in Interpreting Accountability Results for Schools' Facilitation of Parent Involvement Under IDEA. (March 2014) - Elbaum, Batya
Parents' involvement in their child's education has been an important tenet of the Individuals with Disabilities Education Act. Under the special education accountability system that went into effect in 2005, states have been required to report annually to the federal government on the percentage of parents with a child receiving special education services who report that schools facilitated parent involvement. This study investigated the variability of states' reported results owing to states' different choices with regard to items, metrics, and standards used to calculate their percentage on the indicator. Findings indicated that the application of different methodologies could result in reported percentages that vary by as much as 40 percentage points. It is argued that when reported results do not mean the same thing across states, the accountability system may fail in its mission to provide stakeholders with clear information to evaluate program performance and guide improvement efforts.